SIMPEL: A Modernized System for Enhancing Efficiency in Plant Seed Import and Export Licensing - Jessika Aryani Juniarti; Kasahana Indra Pratama; Cheilla Cahya Utami Utami; Nita Merlina; Nissa Almira Mayangky (Journal of Hypermedia & Technology-Enhanced Learning, 2023)
In the era of globalization, PT. XYZ recognizes the importance of developing a licensing system for exporting and importing plant seeds to modernize the current manual recording processes. The existing manual system results in low effectiveness and efficiency, queues during license application, repetitive verification processes, difficulty monitoring license applications, potential fraud between applicants and officials, inaccurate reports on license application outcomes, and negative environmental impacts due to excessive paper usage. This research aims to create the Plant Seed Export and Import Licensing Service Information System (SIMPEL) to enhance licensing services’ speed, accuracy, transparency, and accountability. The development method used is the waterfall method, employing the PHP programming language, Vue.Js as the Frontend framework, Laravel as the Backend, and PostgreSQL as the database. The significance of developing this system lies in the urgency for partner companies to improve operational efficiency and provide optimal licensing services. SIMPEL is designed as a web-based solution that facilitates businesses or applicants in submitting licensing applications online while also providing ease for officials in delivering optimal licensing services. Thus, this research aims to present an information technology solution that aligns with the demands of the times and supports the partner company’s development in adopting digital technology in its operational activities.